Bukayo Saka - Lerwill, Ben Ben Lerwill Ben Lerwill (London Scholastic, 2024)
Be inspired by Football Legend Bukayo Saka! Discover more about how this London-born legend used teamwork, dedication and perseverance to become one of Arsenal's leading players and the youngest member of the England squad. Young football fans will love finding out all about the lives of their favourite players in this incredible biography series. Also in the series: Tammy Abraham, Alex Oxlade-Chamberlain, Harry Kane, Lionel Messi, Erling Haaland and Marcus Rashford. Amazing cover artwork illustrated by Stanley Chow, whose iconic work has found worldwide acclaim.
Keywords: Soccer players